The Ventilatory and Diffusion Dysfunctions in Obese Patients with and without Obstructive Sleep Apnea-Hypopnea Syndrome - Sonia Rouatbi; Ines Ghannouchi; Rim Kammoun; Helmi Ben Saad (Journal of Obesity, 2020)
Objective. To analyze the ventilatory and alveolar-capillary diffusion dysfunctions in case of obesity with or without an OSAS. Methods. It is a cross-sectional study of 48 obese adults (23 OSAS and 25 controls). Anthropometric data (height, weight, and body mass index (BMI)) were collected. All adults responded to a medical questionnaire and underwent polysomnography or sleep polygraphy for apnea-hypopnea index (AHI) and percentage of desaturation measurements. The following lung function data were collected: pulmonary flows and volumes, lung transfer factor for carbon monoxide (DLCO), and fraction of exhaled nitric oxide (FeNO). Results. Obesity was confirmed for the two groups with a total sample mean value of BMI = 35.06 ± 4.68 kg/m2. A significant decrease in lung function was noted in patients with OSAS compared with controls. Indeed, when compared with the control group, the OSAS one had a severe restrictive ventilatory defect (total lung capacity: 93 ± 14 vs. 79 ± 12%), an abnormal DLCO (112 ± 20 vs. 93 ± 22%), and higher bronchial inflammation (18.40 ± 9.20 vs. 31.30 ± 13.60 ppb) (p<0.05). Conclusion. Obesity when associated with OSAS increases the severity of pulmonary function and alveolar-capillary diffusion alteration. This can be explained in part by the alveolar inflammation.